2017
DOI: 10.1016/j.neuropharm.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of alcohol dependence in the context of the addiction cycle

Abstract: Family, twin and adoption studies demonstrate clearly that alcohol dependence and alcohol use disorders are phenotypically complex and heritable. The heritability of alcohol use disorders is estimated at approximately 50–60% of the total phenotypic variability. Vulnerability to alcohol use disorders can be due to multiple genetic or environmental factors or their interaction which gives rise to extensive and daunting heterogeneity. This heterogeneity makes it a significant challenge in mapping and identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 216 publications
4
92
0
1
Order By: Relevance
“…This suggests similar patterns of genetic influence on the effects of early maltreatment on later domestic violence perpetration, a possibility once supported by one of the coauthors in the Caspi et al (2002) study (T. Moffitt, personal communication, November 11, 2002. In addition, the heritability of disorders with known associations with domestic violence, including antisocial personality (Ferguson, 2010), borderline personality (Few et al, 2014), and alcohol use (Reilly, Noronha, Goldman, & Koob, 2017), suggests a range of indirect genetic risk pathways.…”
Section: Developmental and Psychosocial Risk Factors For Domestic Viomentioning
confidence: 99%
“…This suggests similar patterns of genetic influence on the effects of early maltreatment on later domestic violence perpetration, a possibility once supported by one of the coauthors in the Caspi et al (2002) study (T. Moffitt, personal communication, November 11, 2002. In addition, the heritability of disorders with known associations with domestic violence, including antisocial personality (Ferguson, 2010), borderline personality (Few et al, 2014), and alcohol use (Reilly, Noronha, Goldman, & Koob, 2017), suggests a range of indirect genetic risk pathways.…”
Section: Developmental and Psychosocial Risk Factors For Domestic Viomentioning
confidence: 99%
“…Excessive ethanol drinking is a leading cause of preventable death and was estimated to cost the U.S. $249 billion in 2010, $100 billion of which was paid for by the government (1,2). There are genetic factors that increase the propensity for risky drinking (3,4), and genetic background influences the efficacy of treatment options for individuals with AUD (5). In addition, prolonged excessive ethanol intake produces neuroadaptations in projection neurons and neural circuits that are proposed to sustain heavy drinking (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking KCa2 channels in the NAcC with apamin increased voluntary ethanol drinking in mice (13), whereas increasing KCa2 channel function with positive modulators reduced home cage drinking and operant self-administration (11,17). Importantly, the ability of apamin to inhibit KCa2 channel function was completely lost in NAcC MSNs from ethanol 4 dependent mice, but not in rats that had access to 7-weeks of operant self-administration of moderate amounts of ethanol (11). Together, these studies identified KCNN3 as a potential regulator of ethanol consumption and revealed NAcC neuroadaptations in KCa2 channel function that may drive excessive drinking in preclinical rodent models of chronic ethanol exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Strong evidence from family and twin studies demonstrates that alcohol dependence and AUD are phenotypically complex with heritability estimated at approximately 50–60% of total phenotypic variability (Reilly, Noronha, Goldman & Koob, 2017). This degree of heritability is consistent with the polygenic nature of AUD, which includes numerous loci with small effect size.…”
Section: Introductionmentioning
confidence: 99%